Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Chen, Wei-Yu (Ecotoxicology (London, England), 2012)
The impact of environmentally pulsed metal exposure on population dynamics of aquatic organisms remains poorly understood and highly unpredictable. The purpose of our study was to link a dynamic energy budget model to a toxicokinetic/toxicodynamic (TK/TD). We used the model to investigate tilapia population dynamics in response to pulsed waterborne copper (Cu) assessed with available empirical data. We mechanistically linked the acute and chronic bioassays of pulsed waterborne Cu at the scale of individuals to tilapia populations to capture the interaction between environment and population growth and reproduction. A three-stage matrix population model of larva-juvenile-adult was used to project offspring production through two generations. The estimated median population growth rate (λ) decreased from 1.0419 to 0.9991 under pulsed Cu activities ranging from 1.6 to 2.0 μg L(-1). Our results revealed that the influence on λ was predominately due to changes in the adult survival and larval survival and growth functions. We found that pulsed timing has potential impacts on physiological responses and population abundance. Our study indicated that increasing time intervals between first and second pulses decreased mortality and growth inhibition of tilapia populations, indicating that during long pulsed intervals tilapia may have enough time to recover. Our study concluded that the bioenergetics-based matrix population methodology could be employed in a life-cycle toxicity assessment framework to explore the effect of stage-specific mode-of-actions in population response to pulsed contaminants